Political risk management in container shipping : a fuzzy AHP approach - Tan, Tiong Lei (Nanyang Technological University, 2021)
Container volumes are forecasted to grow in Asia, translating to lucrative business opportunities. However, many risks are present in container shipping. In particular, container shipping firms are exposed to political risks, which are not well-covered in academia and is the focus of this study. This study will rank the political risks that container shipping firms face in Asia and the best risk management strategy for each political risk. Government stability, socioeconomic conditions, investment profile, external conflict and internal conflict are the political risks considered while the primary risk management strategies available to manage these risks are avoidance, control and acceptance. Fuzzy analytic hierarchy process was used to rank various political risks. Government stability is found to be the biggest political risk, followed by socioeconomic conditions, internal conflict, investment profile and lastly external conflict. Possible reasons were suggested for the three biggest political risks. Control was selected as the best risk management strategy to manage all the risks. Recommendations were made for container shipping firms and governments to control the political risks.